2017
DOI: 10.1037/adb0000247
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the unique prospective association of negative affect symptoms and adolescent substance use controlling for externalizing symptoms.

Abstract: This systematic review examines whether negative affect symptoms (i.e., anxiety, depression, and internalizing symptoms more broadly) predict subsequent adolescent substance use after controlling for co-occurring externalizing symptoms. Following PRISMA procedures, we identified 61 studies that tested the association of interest. Findings varied depending on the type of negative affect symptom and to some extent on the substance use outcome. The most consistent associations were evident for depressive symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(147 citation statements)
references
References 78 publications
(261 reference statements)
8
133
3
3
Order By: Relevance
“…Overall, a clear association between anxiety and alcohol use was not evident, consistent with previous reviews [24,25]. When distinguishing between alcohol outcomes, anxiety was generally positively associated with AUD, supporting a previous meta-analysis which found that social anxiety was associated with alcohol-related problems [9].…”
Section: Other Evidencesupporting
confidence: 85%
See 3 more Smart Citations
“…Overall, a clear association between anxiety and alcohol use was not evident, consistent with previous reviews [24,25]. When distinguishing between alcohol outcomes, anxiety was generally positively associated with AUD, supporting a previous meta-analysis which found that social anxiety was associated with alcohol-related problems [9].…”
Section: Other Evidencesupporting
confidence: 85%
“…Thirdly, studies in the narrative synthesis may have been too heterogeneous to provide clear combined evidence, a concern raised by other researchers [25]. However, absence of evidence is not evidence of absence.…”
Section: Future Directions and Implicationsmentioning
confidence: 96%
See 2 more Smart Citations
“…(Mojtabai et al, 2016) The increasing rate of depression is of significant concern as suicide rates among adolescents have also increased over time, particularly among female adolescents aged 10 to 14 years in which rates have increased 200% since 1999. (Curtin et al, 2016) In addition to suicide, adolescent depression is associated prospectively with obesity,(Mannan et al, 2016; Zhu et al, 2016) substance use,(Hussong et al, 2017) accelerated atherosclerosis, and early cardiovascular disease. (Goldstein et al, 2015)…”
Section: 0 Introductionmentioning
confidence: 99%